RELATIONSHIP BETWEEN LEARNING MOTIVATION, USE OF LEARNING SOURCES AND ATTENTION OF PARENTS WITH MATHEMATICS RESULTS OF STUDENTS MTs NEGERI GODEAN - Riska Febriyanti Utami; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The low students learning motivation, students do not use learning resources well, and low of parents' attention to children's learning activities were related to students mathematics learning outcomes. This study aims to determine the presence or absence of a positive relationship between and significant relationship between learning motivation, use of learning resources, and parents' attention with the result of mathematics learning outcomes in students class VII on odd semester at MTs Negeri Godean Academic Year of 2015/2016. The population in this study was all students of class VII on odd semester at MTs Negeri Godean Academic Year of 2015/2016 consists of 4 class. While the sample being picked class VII B and test class VII A as a study sample with a random sampling technique to the class. Data were collected by a questionnaire test and methods test. Test research instruments used are the validity test, reliability test, and different power test. The prerequisite test used normally tests, linearity and independent test. Analysis of data using product-moment correlation analysis and linear regression analysis. The result showed that there was a positive and significant correlation between learning motivation, use of learning resources and parent attention with mathematic learning outcomes, multiple correlation coefficient (R) 0,823 with a regression equation Y Ì‚=-33,384+0,427X_1+0,487X_2+0,288X_3, at the 5% significance level, obtained F_count at 19,716 and F_table at 2,95 means F_countâ‰¥F_table. The percentage relative contribution of learning motivation 42,71%, the relative contribution on use of learning 36,33%, and the relative contribution on parents attention 20,97% and then the effective contribution of learning motivation 28,99%, the effective contribution of the use of learning outcomes 24,65%, and the effective contribution of parents attention 14,23 %.